Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Somethinc: Studi Kasus pada Konsumen di Tiktok Shop - Febi Fitria Wulandari; Aji Tuhagana; Dexi Triadinda (Masyarakat Ekonomi Syariah Bogor, 2025)
The increasing intensity of TikTok usage as a marketing platform, along with the growing trend of online skincare product purchases, serves as the background of this study. This research aims to examine the influence of brand image and product quality both partially and simultaneously on consumer purchase decisions for Somethinc skincare (a case study on TikTok Shop consumers). A quantitative verification method was employed, with data collected products through TikTok Shop. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 27. The findings reveal that: (1) brand image positively and significantly impacts purchase decisions; (2) product quality likewise exerts a positive and significant influence on purchase decisions; and (3) simultaneously, brand image and product quality significantly contribute to the purchase decisions of Somethinc skincare products on TikTok Shop.